Effect of parental rearing styles on adolescent ego identity: the mediating role of involutionary attitudes - Ding, Yan; Sun, Changan; Dong, Bo (Frontiers in Psychology, 2024)
Previous studies have found that negative parental rearing styles can negatively predict the acquisition of ego identity, while it has not been discussed whether the overcompetitive attitudes, a stable personality, will further hinder their ego identity development under the model of educational involutionary. The study used the Overcompetitive Attitude Scale, the Brief Parental Rearing Styles Questionnaire, and the Ego Identity Status Scale to investigate 550 young students in a school in Suzhou in order to explore the influence of parental rearing styles on adolescents’ ego identity development and the role of involutional attitudes. The results showed that: (1) Adolescents’ overcompetitive attitude was positively predicted by parental rejection and overprotection, while it was negatively predicted by parental emotional warmth. (2) Parental emotional warmth significantly predicted adolescents’ ego identity status more favorably than parental rejection, overprotection, and overcompetitive attitude. (3) Overcompetitive attitude plays a partial intermediary role between parental rearing style and ego identity.